Design and Simulation Analysis of a New Wheel Hub Drive Single-stage Nutating Reducer for Electric Cars - Wang Xingsheng; Yao Ligang; Wang Yali; Zhang Dawei; Chen Ying (Jixie chuandong)
To solve the problems that the conventional planetary gear wheel hub reducer has many parts, large axial dimensions and complicated installation around the wheel system when the vehicle requires a relatively large transmission， and taking the electric car as the research object, this study proposes a new type of wheel hub drive reducers based on single-stage nutating transmission, describes the working principle and transmission process, completes the structural design and transmission efficiency calculation, and establishes the virtual prototype model. The finite element analysis is carried out to discuss the location and cause of the maximum contact stress of the mechanism under a static load. The reliability and rationality of the structure are verified.